Erythropoietin in anemia of unknown etiology: A systematic review and meta-analysis. Issue 4 (20th April 2016) - Sriram, Swetha; Xenocostas, Anargyros; Lazo-Langner, Alejandro
Abstract : Introduction : We conducted a systematic review and meta-analysis of observational studies in order to explore the relationship between erythropoietin (EPO) and hemoglobin in elderly individuals with anemia of unknown etiology (AUE) and other forms of anemia. Methods : We searched Medline, EMBASE, Web of Science, Biosis Previews, Dissertations, and Theses in addition to meeting abstracts of the European Hematology Association and American Society of Hematology for relevant studies. The meta-analysis was conducted using pooled ratio of means (ROM) through the generic inverse variance method. Results : Six studies were included in the meta-analysis, which confirmed that EPO levels were significantly lower in AUE as compared to iron deficiency anemia (ROM 0.7210; random 95% CI 0.7052 to 0.7372; P -value < 0.00001) and anemia of chronic disease (ROM 0.8995; random 95% CI 0.8362 to 0.9677; P = 0.004). EPO levels in AUE were slightly higher than levels in anemia of chronic kidney disease (ROM 1.0940; random 95% CI 1.0557, 1.1337; P < 0.00001). The heterogeneity (I2) of all analyses was 100%. Conclusion : Our findings suggest that erythropoietin levels in AUE, although elevated, remain inappropriately low, particularly when compared with other forms of anemia. This suggests a relative erythropoietin deficiency or a blunted erythroid cell response.